Micro-Finance for Women Empowerment: A Rural-Urban Analysis - M Saiful Islam; Tarikul Islam (Information Management and Business Review, 2018)
This paper examined the micro-finance services towards empowerment of unprivileged women in the southwestern part of Bangladesh. A sample of 300 low profile unprivileged micro-finance service receiving women equally from rural and urban areas of Khulna district were surveyed during May, 2018. Data were collected on the usage and effectiveness of micro-finance services and were analyzed using STATA 12. Multiple regression model and descriptive statistics were used to interpret data. Economic empowerment, social empowerment, interpersonal empowerment and political empowerment were considered to measure women empowerment. The study found that proper use of microcredit, marital status of women, educational status of women and their husbands, personal income and their position in the family were the main determinants of women empowerment. Women empowerment score remained higher in urban areas than in rural areas. The availability of micro-finance services improved the status of unprivileged low profile suburban women in terms of income generation, saving mobilization, the creation of household assets and overall poverty reduction of rural women. Thus, microfinance has been a useful tool for women empowerment and economic development in both areas but more effective in urban areas.